Usulan Perbaikan Kualitas Tas Aliyen Polo.DR dengan SQC dan FMEA di CV Aliyen Bag - Setiawan, Rizal; Cahyadi, Ujang (Institut Teknologi Garut, 2025)
CV. Aliyen Bag is a company engaged in the production of backpacks. The problem that often occurs in this bag production company is the presence of defective products. The defect tolerance set by the company is 2.5%. In an effort to minimize defects in backpack products, the purpose of this study is to determine the factors that cause product defects and the most dominant defects that can affect product quality. This research uses Statistical Quality Control (SQC) and Failure Mode and Effects Analysis (FMEA) methods. Based on the results of data processing, discussion and analysis, it is obtained that the most dominant factor causing defects is that the machine does not work optimally and the lighting environment is lacking, the most dominant defect is the RPN obtained is 160 which is caused by lack of lighting. This proposed improvement because of the high RPN results in lighting, it is proposed immediately by measuring the lux lighting with the results of 22500 lumens rounded up to 10 lamps with an average of 2300 lumens or 19 W. The implementation of this proposal is expected to improve product quality and minimize the occurrence of product defects, reduce costs due to defects, and increase customer satisfaction with the products produced.